2016
DOI: 10.1016/j.jor.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive osteotomy for a malunited medial Hoffa fracture – A feasible salvage option

Abstract: A 35-year-old male presented with pain and restriction of movements of right knee of 9 months duration. He underwent open reduction and internal fixation for a coronal plane fracture of medial femoral condyle (Hoffa fracture) in another facility 9 months back. Radiological evaluation showed a malunited isolated medial Hoffa fracture. We did an intraarticular osteotomy as a salvage treatment and got a reasonable outcome. This case report analyses the difficulties in the management of this inherently unstable fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
(11 reference statements)
0
20
0
Order By: Relevance
“…Corrective osteotomy after a malunited intra-articular fracture is reported in other parts such as the distal radius and tibial plateau, which led to satisfactory results [6,7]. There are two case reports of corrective osteotomy for the malunited Hoffa fracture [3,4]. They have concluded that the malunited fracture can lead to the restriction of the range of movement, as well as pain and subsequent osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corrective osteotomy after a malunited intra-articular fracture is reported in other parts such as the distal radius and tibial plateau, which led to satisfactory results [6,7]. There are two case reports of corrective osteotomy for the malunited Hoffa fracture [3,4]. They have concluded that the malunited fracture can lead to the restriction of the range of movement, as well as pain and subsequent osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…For the malunion of fractures, salvage corrective osteotomy for extra-articular malunion is often reported, and intra-articular osteotomy for malunited Hoffa fracture (AO/OTA classification 33-B3) is also described [2][3][4]. However, there is no report of osteotomy in multiple segmental malunion of the distal femoral articular fracture.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important differences between the medial and lateral femoral condyles is that the intraosseous blood supply to the medial femoral condyle has limited vascularity compared with that of the lateral femoral condyle [ 4 - 5 ]. The arterial supply of the medial femoral condyle is primarily contributed by the superior medial genicular artery, but the lateral femoral condyle is supplied by both superior and inferior lateral genicular arteries [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lateral condyle is injured three times more frequently than the medial one. The prepotency of the lateral condyle can be attributed to physiological valgus at the knee [ 3 - 4 ]. Generally, Hoffa fractures are seen as a result of a high-velocity, high-energy trauma [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation